2017
DOI: 10.1063/1.4983422
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities of β-glucan (laminaran) against gram-negative and gram-positive bacteria

Abstract: The effect of oyster mushroom (Pleurotus ostreatus) powder as prebiotic agent on yoghurt quality AIP Conference Proceedings 1844, 030006 (2017) Abstract. This study aimed to determine the antibacterial activity of β-Glucan (laminaran) of LAE and LME extracts from brown algae Sargassum crassifolium using HPMS and Ultrasonication against Gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus) and Gram-negative bacteria (Salmonella typhimurium and Escherichia coli). The highest antibacterial activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…β-Glucans also exhibited in vitro antimicrobial activity [ 21 , 22 , 23 ], directly against a broad range of bacterial species, including Escherichia coli , Pseudomonas aeruginosa and Staphylococcus aureus , or indirectly by enhancing macrophage phagocytic activity and resistance to bacterial challenge [ 24 , 25 ]. In another study, β-glucan from oats also showed antimicrobial effects against Escherichia coli and Bacillus subtilis [ 21 ].…”
Section: Wound Healing Activity Of β-Glucans: In Vitro Experimentsmentioning
confidence: 99%
“…β-Glucans also exhibited in vitro antimicrobial activity [ 21 , 22 , 23 ], directly against a broad range of bacterial species, including Escherichia coli , Pseudomonas aeruginosa and Staphylococcus aureus , or indirectly by enhancing macrophage phagocytic activity and resistance to bacterial challenge [ 24 , 25 ]. In another study, β-glucan from oats also showed antimicrobial effects against Escherichia coli and Bacillus subtilis [ 21 ].…”
Section: Wound Healing Activity Of β-Glucans: In Vitro Experimentsmentioning
confidence: 99%
“…They are used in medicine as natural preparations with antitumor properties, which decrease the levels of cholesterol and glucose in the serum and also stimulate the immune system [ 19 , 28 ]. The antibacterial properties of beta-glucans are also known and well described [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], but little is known about their direct action on fungi and possible direct antifungal activity. So far, research has focused on understanding the interactions between host cells (mainly animal) and beta-glucan and the host anti-fungal immunity induced by this compound [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…After 24 hours of incubation on the Luria Bertani broth medium, the medium was centrifuged on 2,500 rpm for 10 min at 4°C. Cell-free supernatants were tested for their antibacterial activity by using the disk-diffusion method [10]. e inhibition zones were observed after 24 hours of incubation.…”
Section: Identification Of Bacteriamentioning
confidence: 99%